Coastal adaptation through urban land reclamation: Exploring the distributional effects - Bisaro, Alexander (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Land reclamation and urban redevelopment is currently underway in coastal regions around the world, as urbanization continues rapidly, and high-value coastal urban land becomes more scarce. Yet coastal hazards will also continue to increase due to sea-level rise, and building flood risk reduction measures into such land reclamation projects appears to be low cost compared to the potential benefits generated. Moreover, land reclamation in high-value urban areas that incorporates such adaptation can generate substantial revenue attractive to governments, particularly in developing countries, which struggle to finance coastal adaptation measures. Yet revenue generation in these projects depends on including some degree of high-value and high-priced developments, giving rise to potential distributional effects. This paper surveys three current coastal urban redevelopment projects incorporating flood risk reduction in the Maldives, Germany and Nigeria, illustrating different modes of urban development projects and the distributional effects that can arise for each of these. The paper explores the equity implications of such projects that arise in planning processes and in implementation. The examples illustrate that inequalities can arise through incentives for corruption, budget imperatives leading to developments that result in gentrification, and shifting of physical risks on to neighboring communities. Finally, I reflect on policy and project design instruments that can address these inequalities, and draw out implications for future research to ensure sustainable and inclusive development of coastal cities in the context of sea-level rise.